Perancangan Sistem Informasi Penjualan & Persediaan Menggunakan Odoo Ver 15 Pada Toko New Palapa Elektronik - Erick Fernando; Meida Sellyvia (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The New Palapa Elektronik store is a shop engaged in the marketing of electronic goods whose main activity is selling various kinds of electronic devices for household needs. Currently at the New Palapa Elektronik Store the process that runs on the sales and inventory process is still manual, namely in the process of making sales invoices, adding up the profits from selling goods in making sales reports, in checking inventory inventory it is necessary to check one by one the items available in the warehouse and it takes a lot of time. For this reason, this research is to design the sales module and inventory module using the Odoo application version 15.0 and system design using the ASAP method. The results of research on sales and inventory system design, can be used to display stored information, automate and provide information on the amount of profits from the sales report process and stock inventory reports.